Entrepreneurial Behaviour Wirausaha Keripik Pisang: Tinjauan Lingkungan Keluarga dan Efikasi Diri - Marianti, Winda; LV, Yuhendri (Lembaga Yasin AlSys, 2023)
Entrepreneurship can be a job choice for the workforce. Entrepreneurship is profitable for business managers in terms of turnover and creating jobs. One of the sectors that is favored by Solok Selatan Regency is banana chip SMEs which produce typical South Solok Selatan food. The problem of this research is that banana chip entrepreneurs in Solok Selatan Regency have not had good entrepreneurial behavior, the impact of this banana chip business is seen from the number of entrepreneurs who have gone out of business. Based on this, it is necessary to study the influence of the family environment and self-efficacy on the entrepreneurial behavior of MSME banana chips in Solok Selatan Regency. Respondents in this study were banana chip entrepreneurs in Solok Selatan Regency with a sampling technique using proportional random sampling. The instrument in this study was a questionnaire. The data analysis technique used is path analysis. The results of this study indicate that the family environment influences entrepreneurial behavior through self-efficacy. Thus the family environment and self-efficacy play an important role in shaping entrepreneurial behavior. The results of this study can be used as a guideline for the Solok Selatan Regency MSME Service in formulating policies for banana chip entrepreneurs in increasing entrepreneurial behavior for the sustainability of the banana chip business.